Hazards identification at bus interchanges in Kuala Lumpur - Che Hassan, Che Rosmani; Hamid, Mahar Diana; Dzulkifly, Norazlin; Mahmood, Noor Zalina (Taylor's University, 2009)
Bus is one of the main alternatives of mass public transportation in Kuala Lumpur as it is cheaper and has better coverage area than its counterparts such as Light Rapid Train (LRT) and commuter train. Thousands of people use the bus interchanges around Kuala Lumpur to reach their destinations. In this paper, hazards at these bus interchanges are identified to prevent or, at least to minimize the number of accidents that might occur as well as to reduce health problem. Five bus interchanges were selected for this research; the Hentian Puduraya, Klang Bus Stand, Hentian Putra, Mydin Bus Stand and Hentian Duta. The main objective of this research is to study the level of safety awareness among the management of the bus interchange and also the public. This research is conducted using several methods, which includes observation, checklist, questionnaire and interviews with safety personnel. From the result, it was found that most users of these bus interchanges are aware of safety aspects and this might be due to an increasing level of education. Hazards that might occur at these bus interchanges have also been identified and several suggestions to prevent or minimize these hazards have been made. Â© School of Engineering, Taylor's University College.